THE CURRENT STATE AND TRENDS OF INTERNATIONAL COOPERATION OF NRU BELSU - Mikhail A. Trubitsyn (Moscow Polytechnic University, 2016)
The article focuses on the main aspects of international cooperation of Belgorod State National Research University aimed at increasing its internationalization level. In order to achieve the goals specific measures are introduced by NRU BelSU in three basic areas: 1) extension of export of educational services for the purpose of international students' recruitment for study; 2) development and realization of joint educational programs and projects with foreign partners; 3) support and increase of bilateral academic mobility of students and teaching staff. Detailed information on international student body, numbers of academic mobility of students and teaching staff, collaboration with partner universities and implementation ofjoint educational programs are specified. The Program ofForeign Languages Education is put forward as an important instrument of internationalization.